Heterogeneity and influencing factors of pore structure in different coal ranks - Yuewen ZHU; Fuhua SHANG; Shuwei MA; Han ZHANG; Yanming ZHU; Meng WANG; Yingying MA; Weiqing LI; Wending FU (Meitan kexue jishu, 2025)
To study the pore structure heterogeneity and influencing factors of different coal ranks, 8 coal samples with different coal ranks were tested through low-temperature N2 and CO2 adsorption experiments. The fractal dimension of different coal ranks was calculated using the Frenkel-Halsey-Hill (FHH) model, the evolution law of fractal dimension in coalification was analyzed and the influence of coal quality on the fractal characteristics of pore structure was explored based on the characteristics of coal quality. The results show that: ① In the coalification process, the moisture and volatile matter in coal gradually decrease, and the fixed carbon content gradually increases, while the ash yield has no significant correlation with coalification. ② The mesoporous parameters of coal have no significant correlation with maturity, while the micropore parameters exhibit a U-shaped change trend with the increase of maturity, that is the microporous parameters first gradually decrease and then gradually increase after the second coalification jump. ③ The fractal dimensions D1, D2 and Dc of different coal ranks are generally closely related to coalification, with the highest correlation observed in the microporous fractal dimension Dc (R2=0.7092), which is mainly related to the formation of abundant secondary pores during the thermal evolution process. ④ The fractal dimensions D1, D2 and Dc have no significant correlation with moisture content and ash yield, while have a negative correlation with volatile matter and fixed carbon content, which is closely related to the change in coal quality during coalification. The study result can provide a significant reference basis for the evaluation of coalbed methane resources in different coal ranks.